Adjusting Assessment Techniques During the Covid-19 Pandemic - Try Andreas Putra, Aris; Fatimah Kadir, St.; Hewi, La; Armeth Daud Alkahar, Aris; Sufiani, Sufiani; Agus, Imaludin (KnE Social Sciences, 2022)
During the Covid-19 pandemic, the learning system needed to be reconditioned, which included the selection of assessment techniques. This article aimed to determine and explain the adjustments of the assessment techniques selected and used by the lecturers of FATIK at IAIN Kendari during the Covid-19 pandemic. This was quantitative research and data were collected through questionnaires. Descriptive statistical analyses were used. This research was conducted at FATIK in IAIN Kendari and involved a sample of 200. The results revealed that: (1) generally, lecturers made adjustments to the assessment techniques during the Covid-19 pandemic; 2) the ‘assignment assessment’ technique was that used by the highest proportion of lecturers, which included the assessment of learning activities, midterm exam assessment, and semester final exams; (3) the ‘performance appraisal’ technique was used by the fewest lecturers; and (4) the assessment technique favoured most and recommended by students at the Faculty of Tarbiyah in IAIN Kendari was the ‘initiation of assignments’. Based on the results of this study, there was no one assessment technique that was the best, but the selection of assessment techniques was based on the conditions that surrounded them. Keywords: adjustment, assessment techniques, Covid-19 pandemic